Estimativa do potencial de geração fotovoltaica do campus do Pici da UFC - Costa, Douglas Aurélio Carvalho (2018)
The present dissertation aimed at estimating the photovoltaic (PV) generation potential at the Pici Campus of the Federal University of Ceará (UFC). Data collected during the period of one year - September 2016 to August 2017 - were evaluated on a photovoltaic (PV) distributed generation (DG) connected to the distribution network of the Pici Campus/UFC and the irradiation in the vicinity of the PV DG. Representative day charts were plotted for each month in the sample period. The annual average irradiance (l gmês m), average electricity generation (Gmês m), average PV capacity factor (FCmed) and PV efficiency (eFV) for the study region were of 5.21 kWh/m²/day, 7.55 kWh/day (0.7754 kWh/m²/day), 20.98% and 14.94%, respectively. The equivalence in the reduction of 2 provided by the PV DG (ECO2) in the LEA in the period studied was 255.64 kgCO2/year. The analysis of the PV potential of the Pici Campus was done with a focus on the ceilings of the buildings of the Technology Center (CT-UFC), Science Center (CC-UFC), Agricultural Science Center (CCA-UFC), Institute of Culture and Art/University Restaurant (ICA-UFC/RU-UFC) and University Library (BU-UFC), which are separated into five "sets" of areas that have a PV generation potential of 2.67 GWh/year, 4.80 GWh/year, 1.97 GWh/year, 2.25 GWh/year and 0.55 GWh/year respectively, totaling a PV potential of 12.25 GWh/year, with a total installed capacity of 6.67 MWp. For case 1, cost of PV DG in the Pici Campus based on the Investment of the Federal Institute of Ceara (IFCE), the investment for the implementation of the PV DG system (CFV) is R$ 29,262,587.57. For Case 2, cost of PV DG in the Pici Campus based on the Investment in the solar park of Nova Olinda, Piauí, the required investment is R$ 20,400,732.78. The amount of the invoice for the Campus do Pici in this period was R $ 8,330,313.61. The consumption of electric energy was 14.33 GWh, with 1.19 GWh consumed in peak time (HP) and 13.14 GWh consumed in the off-peak time HFP. The average Gmês m of the Pici Campus is able to offset R $ 5,047,425.79 (93.29%) of the value of energy consumption in the HFP. The return period of the PV DG (PRIFV) investment installed in the Pici Campus is from four to six years.